2004
DOI: 10.1002/asna.200310204
|View full text |Cite
|
Sign up to set email alerts
|

A new photometric study of CW Cephei and its apsidal motion

Abstract: Abstract. New photoelectric observations of the eccentric orbit binary CW Cephei have been carried out in B, V and R colours during the 2000 observing season at TÜBITAK (The Scientific and Technical Research Council of Turkey) National Observatory. The light curves of the system were analyzed with a nonsynchronous rotation approach using the method of Wilson-Devinney in B, V and R bands, simultaneously. Especially, we used the R band to check for a third light in the solution as distinct from previous studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…Such a component of a spectral type K5 with bolometric magnitude m 3 = 6.8 mag produces the third light of L 3 = 0.0005% only, which is still in contradiction with the contribution of the third light of about 3-5% given in Han et al (2002) or about 1% derived by Erdem et al (2004).…”
Section: Cw Cepcontrasting
confidence: 76%
See 1 more Smart Citation
“…Such a component of a spectral type K5 with bolometric magnitude m 3 = 6.8 mag produces the third light of L 3 = 0.0005% only, which is still in contradiction with the contribution of the third light of about 3-5% given in Han et al (2002) or about 1% derived by Erdem et al (2004).…”
Section: Cw Cepcontrasting
confidence: 76%
“…A detailed study of the apsidal motion of CW Cep was recently carried out by Erdem et al (2004), but we decided to perform a re-analysis in light of the new times of minima now available. Besides those given in Table 1, we have added the times of minimum obtained by Han et al (2002, their Table 1), Agerer & Hübscher (2003), Hübscher (2005), and Hübscher et al (2005).…”
Section: Cw Cepmentioning
confidence: 99%
“…This problem has been extensively discussed by Clausen & Gimenez (1991), who found that the spread in radii ratios is also accompanied by a significant spread in the sum of the radii. Subsequent analysis of their own new photometry by Han et al (2002) and Erdem et al (2004) did not settle issue as they used a different methodology from Clausen & Gimenez (1991). Specifically, Han et al (2002) did not prefer the photographically determined light ratio over that returned from the light curve modelling, and Erdem et al (2004) allowed for the possibility of asynchronous rotation in the components, which alters the light ratios derived from photometric modelling.…”
Section: Cw Cepheimentioning
confidence: 99%
“…Subsequent analysis of their own new photometry by Han et al (2002) and Erdem et al (2004) did not settle issue as they used a different methodology from Clausen & Gimenez (1991). Specifically, Han et al (2002) did not prefer the photographically determined light ratio over that returned from the light curve modelling, and Erdem et al (2004) allowed for the possibility of asynchronous rotation in the components, which alters the light ratios derived from photometric modelling. Comparing the radii derived by different previous analyses (a complete set of the references are given in Han et al 2002), a spread of ∼8% is found.…”
Section: Cw Cepheimentioning
confidence: 99%
“… *(1) Kozyreva, Kusakin & Khaliullin (2005), (2) Wolf & Zejda (2005), (3) Bozkurt (2000), (4) Kozyreva et al (1999), (5) Erdem et al (2004), (6) Wolf et al (2006), (7) Wolf, Diethelm & Hornoch (2001), (8) Değirmenci et al (2003), (9) Wolf et al (2002), (10) Khaliullin & Khaliullina (2002), (11) Wolf et al (1999), (12) Bozkurt & Değirmenci (2002), (13) Alencar et al (1997), (14) Wolf (2000), (15) González et al (2005), (16) Wolf, Diethelm & Zejda (2005) and (17) Bozkurt (2006). …”
Section: Triple Systems Showing Apsidal Motionmentioning
confidence: 99%